Talking about good and bad learners: Linguistic dimension of implicit theories of intelligence - Bernardo, Allan B.I. (Animo Repository, 2012)
Introduction: Implicit theories of intelligence are lay beliefs about whether intelligence is either fixed (entity theory) or changeable (incremental theory), and are known to be important predictors of learning processes of students in schools. Four studies test the hypothesis that objectifying linguistic practices (i.e., the use of abstract linguistic categories) are associated with belief in the entity theory of intelligence, but not in incremental theory. Method: In each study students were identified as either entity or incremental theorists, and the linguistic features of their written descriptions of good and bad learners were analyzed and compared. Results: In all four studies, students identified as entity theorists use more nouns and adjectives but fewer verbs and contextual references in their descriptions of good and bad learners, exemplifying the objectifying linguistic practice. Students identified as incremental theorists showed the reverse pattern. Discussion and Conclusion: The results suggest a linguistic dimension to implicit theories of intelligence. The results are discussed in terms of possible similar cognitive approaches that underlie both linguistic practices and implicit person theories of intelligence. Implications for how teachers and parents talk about their assessment of students' learning and achievement are discussed. © Education & Psychology I+D+i and Editorial EOS (Spain).